A comprehensive clinical evaluation of levocetirizine in the treatment of chronic urticaria in children - Lu, Liu; Xiaodan, Zhang; Chang, Liu; Meixing, Yan (Frontiers in Pharmacology, 2025)
ObjectiveLevocetirizine is a second-generation antihistamine that is the first-line drug recommended by the guidelines for the treatment of chronic urticaria in children. However, the current study focused mainly on adults, and a comprehensive evaluation of children has not been reported. Therefore, comprehensive clinical evaluation of levocetirizine in the treatment of chronic urticaria in children is crucial for providing rational clinical drug use and improving the basis of relevant national policies. To conduct a comprehensive clinical evaluation of levocetirizine in the treatment of chronic urticaria in children and provide a reference for rational drug use and related policy decisions in clinical practice.MethodsA comprehensive clinical evaluation index system for the use of antiallergic drugs in children was established via a literature review, expert interviews, and the Delphi method. Evidence was collected to evaluate the safety, efficiency, economy, suitability, accessibility and innovation of levocetirizine and loratadine for the treatment of chronic urticaria in children.ResultsThe comprehensive clinical evaluation index system included six primary indicators, 12 secondary indicators, and 25 tertiary indicators. The total clinical comprehensive evaluation score of levocetirizine was 92.83, whereas that of loratadine was 72.49. The former is superior to the latter in terms of safety, effectiveness, suitability, innovation, and accessibility, whereas the latter is more cost-effective than the former.ConclusionThe comprehensive clinical value of levocetirizine is greater than that of loratadine in the treatment of chronic urticaria in children, which can provide evidence for the rational use of antiallergic drugs and drug catalog selection in medical institutions.